Model scaffolding pembelajaran menulis dengan pendekatan proses bagi anak tunarungu - Yuliyati, Yuliyati; Purbaningrum, Endang (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The aims of this research are (1) to describe the needs analysis and challenges and (2) to produce a scaffolding draft model for teaching writing using a process approach combined with the Reflective Maternal Method (MMR). This research and development study applies the R2D2 model, which emphasizes user needs based on contextual conditions (teachers and students with disabilities) and is developed collaboratively. Based on the needs analysis conducted in the first year, a scaffolding draft model was produced using a process approach elaborated with the Reflective Maternal Method (MMR).